Effectiveness of Advertisements in India: An Empirical Study - Raina, Dalip; Khajuria, Kritika (Indian Journal of Marketing, 2012)
This paper explores the effectiveness of advertising in India in the current scenario. The study examines the motive behind purchase of a product, major component of the advertisement, and to what extent the advertisements carry a relevant and believable message. For this purpose, primary survey was done, and the data was collected from 220 respondents from Jammu with the help of a well-designed pre-tested structured questionnaire. The analysis concluded that there is a significant impact of advertisement on these parameters. The customers have a positive perception towards advertising as they find it more satisfactory to invest in a product after watching the advertisement. It is also concluded that the advertisements’ messages should be relevant as consumers consider them while taking buying decisions.